A prospective, multicentric study to determine the safety and effectiveness of fixed-dose combination of camylofin dihydrochloride and nimesulide in patients presenting with acute colicky abdominal pain in India - Jadhav, Kirankumar; Shukla, Vineet; Kumar, Anil; Kalita, Partha P.; Borthakur, Swapnav (International Journal of Advances in Medicine, 2022)
Background: Spasmolytics and NSAIDs are a therapy of choice in colic pain. However, the tolerability and effectiveness of this combination remains unexplored. The aim of this prospective, single-arm, open label, multicenter study was to evaluate the safety and effectiveness of Anafortan-N® (fixed-dose combination of camylofin dihydrochloride 50 mg + nimesulide 100 mg) in patients with acute colicky abdominal pain. Methods: In all, 295 patients with acute colicky abdominal pain and at least one episode of colicky pain in the last 24 hours were enrolled in this study. None of the patients were hospitalized. All patients were advised Anafortan-N® tablets twice daily orally for 5 days. The safety of Anafortan-N® was assessed by number and percentage of patients with adverse events (AEs) and change in the severity and frequency of AEs by the end of treatment. The tolerability was determined by number and percentage of patients who had to discontinue the treatment due to AEs. The effectiveness was evaluated as percentage change in the mean intensity of pain score (based on a 100-mm visual analog scale) from baseline to end of treatment. Results: Overall, 14 (4.7%) patients reported 14 AEs, all of which were treatment-emergent and non-serious. Of the 14 AEs, 7 AEs were mild, 6 AEs were moderate, and 1 AE was severe. No serious adverse events (SAEs) were reported. No adjustment of the study medication was required in response to any of the AEs, and none of the AEs led to discontinuation of the study treatment. At end of treatment (EOT), the pain intensity significantly (p<0.0001) reduced to 1.7±5.49 with a mean change of -69.9±17.42 from baseline, and the daily pain intensity significantly (p<0.0001) reduced to 0.1±0.38 with a mean change of -3.5±1.77 from baseline. Conclusions: Among Indian patients presenting with acute abdominal colicky pain, twice daily treatment with a FDC of camylofin dihydrochloride 50 mg and nimesulide 100 mg (Anafortan-N®) showed significant reduction in pain intensity with very few side effects, thereby confirming its safety, tolerability, and effectiveness in acute colicky abdominal pain.